Physical factors affecting plasmid DNA compaction in stearylamine-containing nanoemulsions intended for gene delivery - Silva, André Leandro; Alexandrino Jr., Francisco; Verissimo, Lourena Mafra; Agnez-Lima, Lucymara Fassarella; Egito, Lucila Carmem Monte; Oliveira, Anselmo Gomes de [UNESP]; do Egito, Eryvaldo Socrates Tabosa (MDPI, 2012)
Cationic lipids have been used in the development of non-viral gene delivery systems as lipoplexes. Stearylamine, a cationic lipid that presents a primary amine group when in solution, is able to compact genetic material by electrostatic interactions. In dispersed systems such as nanoemulsions this lipid anchors on the oil/water interface confering a positive charge to them. The aim of this work was to evaluate factors that influence DNA compaction in cationic nanoemulsions containing stearylamine. The influence of the stearylamine incorporation phase (water or oil), time of complexation, and different incubation temperatures were studied. The complexation rate was assessed by electrophoresis migration on agarose gel 0.7%, and nanoemulsion and lipoplex characterization was done by Dynamic Light Scattering (DLS). The results demonstrate that the best DNA compaction process occurs after 120 min of complexation, at low temperature (4 ± 1 °C), and after incorporation of the cationic lipid into the aqueous phase. Although the zeta potential of lipoplexes was lower than the results found for basic nanoemulsions, the granulometry did not change. Moreover, it was demonstrated that lipoplexes are suitable vehicles for gene delivery. © 2012 by the authors; licensee MDPI, Basel, Switzerland.
Keywords: Cationic lipid nanoemulsions; Gene therapy; Stearylamine; lipid; octadecylamine; plasmid DNA; complex formation; electrophoresis; incubation time; light scattering; low temperature; nanoemulsion; nonviral gene delivery system; particle size; temperature sensitivity; zeta potential